Influence of Trust, User Experience, and Service Quality on Customer Satisfaction among Shopee Users in Surabaya - Rafinsyah Achmad; Azizah Nurul (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to determine and analyze the effect of trust, user experience, and service quality on Shopee customer satisfaction in Surabaya. This research uses a quantitative approach with data collection carried out through the distribution of questionnaires. The sample used in this study consisted of 150 respondents from the Surabaya community, determined using the Non-Probability Sampling-Purposive Sampling technique. Data analysis was conducted using multiple linear regression analysis methods with SPSS 25 statistical software for Windows. The results show that trust, user experience, and service quality simultaneously have a significant effect on Shopee customer satisfaction in Surabaya. User experience and service quality individually have a significant effect on Shopee customer satisfaction in Surabaya. However, trust individually does not have a significant effect on Shopee customer satisfaction in Surabaya. These results highlight the importance of user experience and service quality in enhancing customer satisfaction. Shopee can focus on improving these two aspects to strengthen customer relationships and achieve sustainable business success. Additionally, Shopee is expected to maintain and increase customer trust by ensuring that the platform remains safe and reliable.